Review of the Role of Metabolic Factors in Determining the Post-surgical Adhesion and its Therapeutic Implications, with a Focus on Extracellular Matrix and Oxidative Stress - Tavakkoli, Mahmoud; Khodashahi, Rozita; Aliakbarian, Mohsen; Rahimi, Hoda; Ashrafzadeh, Kiarash; Ferns, Gordon; Khaleghi, Ebrahim; Arjmand, Mohammad-Hassan (Current Molecular Pharmacology, 2024)
The potential role of metabolic reprogramming in fibrogenesis has recently attracted interest. Extracellular matrix stiffness, inflammation, and subsequent oxidative stress are essential mediators in the causation of fibrosis. The prevention of post-surgical adhesion is a challenge in medicine. It is defined as a fibrotic disorder in which adhesive bands develop after abdominal or pelvic surgery. Despite many studies related to the pathogenesis of post-surgical adhesion (PSA), many unknowns exist. Therefore, evaluating different pathways may help characterize and identify the cause of fibrotic scar formation post-operation. Glucose and lipid metabolism are crucial metabolic pathways in the cell’s energy production that may be targeted by hypoxia-induced factor alpha and profibrotic cytokines such as TGF-β to mediate fibrogenesis. Inhibition of upregulated metabolic pathways may be a viable strategy for ameliorating post-surgical adhesion. In this review, we have discussed the potential role of altered glucose and lipid metabolism in extracellular matrix (ECM) stiffness and oxidative stress as crucial mediators in fibrosis.
Keywords: Fbrosis